2022
DOI: 10.1038/s41598-022-10500-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel polypeptide-modified fluorescent gold nanoclusters for copper ion detection

Abstract: Biomolecule-functionalized fluorescent gold nanocluster (AuNCs) have attracted a lot of attention due to good biocompatibility, stable physicochemical properties and considerable cost advantages. Inappropriate concentration of Cu2+ may cause a variety of diseases. In this study, AuNCs were synthesized in alkaline aqueous solution using bovine serum albumin (BSA) as a template. And then, the peptide CCYWDAHRDY was coupled to AuNCs. Furthermore, the fluorescence of synthesized CCYWDAHRDY-AuNCs response to Cu2+ w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…After being complexed by the peptide, Cu 2+ , with a paramagnetic property, quenched the fluorescence of the dansyl group near the binding center via electron or energy transfer from the excited fluorophore to the coordinated Cu 2+ . In addition, metal NCs as the fluorescent reporters have attracted extensive attention because of their promising properties (e.g., easy synthesis, good biocompatibility, and high stability) [ 36 , 37 , 38 ]. In order to evaluate the selectivity and anti-interference of the sensor, other common metal ions (K + , Na + , Mg 2+ , Fe 2+ , Cu + , Co 2+ ) and plasma were determined as the control experiments.…”
Section: Fluorescent Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…After being complexed by the peptide, Cu 2+ , with a paramagnetic property, quenched the fluorescence of the dansyl group near the binding center via electron or energy transfer from the excited fluorophore to the coordinated Cu 2+ . In addition, metal NCs as the fluorescent reporters have attracted extensive attention because of their promising properties (e.g., easy synthesis, good biocompatibility, and high stability) [ 36 , 37 , 38 ]. In order to evaluate the selectivity and anti-interference of the sensor, other common metal ions (K + , Na + , Mg 2+ , Fe 2+ , Cu + , Co 2+ ) and plasma were determined as the control experiments.…”
Section: Fluorescent Biosensorsmentioning
confidence: 99%
“…Qian et al developed a Cu 2+ biosensor by using the peptide of lipoic acid-Arg-Gly-Asp-Asp-Lys-lipoic acid (LA-RGDK-LA) as the templet and ligand to synthesize AuNCs [ 37 ]. Zhuang et al reported the detection of Cu 2+ with the peptide (CCYWDAHRDY)-modified AuNCs, in which bovine serum albumin (BSA) was used as the template for the synthesis of fluorescent AuNCs [ 38 ]. The binding of Cu 2+ ions to the peptide-modified AuNCs caused the fluorescence quenching.…”
Section: Fluorescent Biosensorsmentioning
confidence: 99%
“…To understand the sensing mechanism we have measured the hydrodynamic diameter (D h ) and excited state life times (τ) of the both clusters during gradual addition of some selected metal salts. In general the luminescence quenching phenomenon occurs through photo-induced electron transfer (PET) process via static or dynamic interaction between probe and the analyte [40][41][42][43][44][45][46][47][48]. However, the turn-on sensing is uncommon and the underlying mechanism may be very distinct for different probes [49][50][51].…”
Section: Dynamic Light Scattering (Dls) and Tcspc Analysismentioning
confidence: 99%
“…The detection of trace quantity of metal ions is important as their contamination in food, drinking water and in body uids is very important from human health safety and diagnostic prospective. The advantages of luminescence sensing of analytes includes very high sensitivity and selectivity, low cost, on the spot testing feasibility and fast response time [38] Luminescence quenching (Turn-OFF) is the most dominant pathway of sensing analytes demonstrated by various metal clusters and we may ascribe its origin through electron/energy transfer from metal cluster to analyte through a static or dynamic adduct formation mechanism [44][45][46][47][48]. Luminescence enhancement (Turn-ON) based sensing of analytes is more advantageous but is less common and it follows a distinct mechanism than the previous one [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, absorption, fluorescence and electrochemical methods are used frequently in chemical analysis ( 1 , 2 ). Zhuang et al ( 3 ) reported a peptide fluorescent probe TP-2 (TPE-TrP-Pro-GlN-His-Glu-NH 2 ), which utilized an aggregation-induced emission effect and afforded high selectivity in the determination of Hg 2+ , the detection limit (DL) being 41 nM. Yu et al ( 4 ) immobilized an antibody against C-peptide onto TRF microspheres in a directional manner, thus fully exposing the antigen binding site, to determine C-peptide in human serum with a DL of 0.005 ng/mL.…”
Section: Introductionmentioning
confidence: 99%